2008
DOI: 10.1680/geot.2008.58.1.55
|View full text |Cite
|
Sign up to set email alerts
|

Shear strength model for overconsolidated clay-infilled idealised rock joints

Abstract: Saturated infilled joints can contribute to the instability of rock masses during undrained shearing. This paper reports an experimental investigation into the effect of the overconsolidation of infilled rough joints on undrained shear behaviour. A revised model is presented for predicting the shear strength of rough infilled joints on the basis of experimental tests carried out on idealised sawtoothed joints with natural silty clay as the infill material. Tests were conducted under consolidated undrained cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
46
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(47 citation statements)
references
References 12 publications
1
46
0
Order By: Relevance
“…ese soft fillings significantly weaken the shear strength of jointed rock and make the rock present more obvious heterogeneity and anisotropy. Infilled joints generally become the weakest position under shear which will easily trigger the whole instability of engineering rock [1][2][3][4]. erefore, the study of shear properties of infilled joints is of significance in both stability evaluation and reinforcement of engineering rock.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…ese soft fillings significantly weaken the shear strength of jointed rock and make the rock present more obvious heterogeneity and anisotropy. Infilled joints generally become the weakest position under shear which will easily trigger the whole instability of engineering rock [1][2][3][4]. erefore, the study of shear properties of infilled joints is of significance in both stability evaluation and reinforcement of engineering rock.…”
Section: Introductionmentioning
confidence: 99%
“…ese influenced factors mainly included material type, surface morphology, initial normal stress, infilled ratio, fillings saturation degree, and overconsolidation degree [1,[5][6][7]. Previous test results showed that soft fillings, such as Green mudstone, serpentinite, and clay, will significantly reduce the shear strength of infilled joints [8], while the high-strength fillings, such as mortar and concrete, enhance the shear strength [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the past 30 years much more information has become available on the shear behavior of joints infilled with soil material. Several models have been proposed to predict the shear strength of infilled joints under both constant normal load (CNL) and constant normal stiffness (CNS) boundary conditions, considering the ratio of infill thickness (t) to the height of the joint wall asperity (a), i.e., t/a ratio [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. The experimental researches to date have tended to focus on modelled joints or replicas rather than natural rock joints.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, when the infilling material is sufficiently thick, the shear strength is defined only by the friction angle of the infilling material. Equation 2-16 was further modified so as to take into consideration an influence of consolidation of infilling materials by Indraratna, Jayanathan, and Brown (2008). The revised equation is given as:…”
mentioning
confidence: 99%